Three new brachypterous species of the genus Coleolissus (Coleoptera: Carabidae) from China and India - Kataev, Boris M.; Wrase, David W. (Zootaxa, 2023)
Three new obligatory brachypterous species of the genus Coleolissus Bates, 1892 are described: Coleolissus curtus sp. n. from the southern Gaoligong Mountain Range (Yunnan, China), C. cognatus sp. n. from the Wuliangshan Mountain Range (Yunnan, China), and C. brevis sp. n. from the environs of “Khecheoparin” (Sikkim, India). The relationships of these species are discussed.